2013
DOI: 10.1007/s10764-013-9729-1
|View full text |Cite
|
Sign up to set email alerts
|

Negotiations over Grooming in Wild Vervet Monkeys (Chlorocebus pygerythrus)

Abstract: Mutual grooming plays a central role in the establishment and maintenance of social relationships in primates. Allogrooming has two main functions: hygiene and bonding with partners. The duration of grooming bouts is commonly used in studies of the functional aspects of grooming, but few reflect on the proximate mechanisms that determine grooming bout lengths. As it is highly unlikely that groomer and groomee prefer exactly the same bout length, we are likely to observe the result of some form of negotiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…The reason for intergroup variation in this signal, observed in the context of an adult female grooming another with her mouth, remains unclear. The authors explain lip smacking as a request for tolerance when directed to a higher‐ranked individual, or as an appeasement signal when directed to a lower‐ranked individual (van de Waal, Spinelli, et al, ), but this did not explain the variation found between the two study groups. Though the explanation remains unclear, I suggest deeper consideration of this group‐level variation.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The reason for intergroup variation in this signal, observed in the context of an adult female grooming another with her mouth, remains unclear. The authors explain lip smacking as a request for tolerance when directed to a higher‐ranked individual, or as an appeasement signal when directed to a lower‐ranked individual (van de Waal, Spinelli, et al, ), but this did not explain the variation found between the two study groups. Though the explanation remains unclear, I suggest deeper consideration of this group‐level variation.…”
Section: Resultsmentioning
confidence: 93%
“…Mean lip smacks per second performed by groomers during grooming‐with‐mouth events in relation to the recipient’s rank. The dashed lines represent the linear trend lines (Figure 7 in van de Waal, Spinelli, et al, )…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations